Nanostar probes for tip-enhanced spectroscopy. Issue 2 (14th December 2015) - Kim, Woong; Kim, Nara; Park, Joon Won; Kim, Zee Hwan
Abstract : A nanostar probe for tip-enhanced near field optical microscopy. Abstract : To overcome the current limit of tip-enhanced spectroscopy that is based on metallic nano-probes, we developed a new scanning probe with a metallic nanostar, a nanoparticle with sharp spikes. A Au nanoparticle of 5 nm was first attached to the end of a tip through DNA–DNA hybridization and mechanical pick-up. The nanoparticle was converted to a nanostar with a core diameter of ∼70 nm and spike lengths between 50 nm and 80 nm through the reduction of Au 3+ with ascorbic acid in the presence of Ag + . Fabrication yields of such tips exceeded 60%, and more than 80% of such tips showed a mechanical durability sufficient for use in scanning microscopy. Effectiveness of the new probes for tip-enhanced Raman scattering (TERS) and tip-enhanced fluorescence (TEF) was confirmed. The probes exhibited the necessary enhancement for TEF, and the tip-on and tip-off ratios varied between 5 and 100. This large tip-to-tip variability may arise from the uncontrolled orientation of the apexes of the spike with respect to the sample surface, which calls for further fabrication improvement. The result overall supports a new fabrication approach for the probe that is effective for tip-enhanced spectroscopy.